Precipitation isotopic information: A tool for building the data base to verify milk geographical origin traceability. (January 2020) - Behkami, Shima; Gholami, Rima; Gholami, Mehrdad; Roohparvar, Rasool
Abstract: Isotopic composition of milk is affected by various environmental factors one of which is precipitation. Therefore, an attempt was made to investigate the effectiveness of precipitation isotopic information in order to build milk geographical origin data base. It was observed that there was significantly high correlation between δ 2 H data and δ 18 O data of milk with that of the precipitation as well as correlations between C and N content in the milk with that of latitude which enables clustering of milk samples based on their geographical origin. Meanwhile, H and O isotopic data were used as a potential tool for building database for geographical traceability of milk. As a conclusion, by applying factorial analysis a clear separation based on region of origin was observed which enables the grouping of samples in two clusters, namely north and south. Highlights: Distribution of δH, δO, δN and δC in raw cow milk samples. Isotopic ratio variation of O and H in precipitation samples. Strong correlation between δH and δO in milk with that of precipitation. Ascertaining geographical origin of milk using δ (H, C, N and O) information. δO and δH of precipitation used to build the database of milk traceability.